Evaluation of the stability of hydrocortisone sodium succinate in solutions for parenteral use by a validated HPLC-UV method - Mihovec, Katja (Acta chimica slovenica, 2022)
This study aimed to determine the in-use stability (t95%) of hydrocortisone sodium succinate (HSS) infusion solutions and provide evidence-based guidelines on their usability. HSS infusion solutions were prepared and stored as recommended by the manufacturer and under common conditions in our hospital. The effects of HSS concentration (1 and 4 mg/mL), solvent (isotonic saline and glucose), temperature (ambient and 30°C), and light on its stability were evaluated using a validated stability-indicating HPLC-UV method. HSS degradation followed first-order kinetics. No significant difference in its stability was observed between the two evaluated concentrations, solvents and light exposure (t95% between 25 and 30 h). Elevated temperature (30°C) affected HSS stability and significantly reduced the t95% (4.6-6.3 h). HSS infusion solutions are physically and chemically stable (?5% degradation) for at least 6 h if stored below 30°C. The in-use stability may be extended up to 24 h if stored below 24°C.
Keywords: forced degradation study; infusion; infuzija; injection; injekcija; in-use stability; Kromatografska analiza; Raztopine; rok uporabnosti po odprtju; Solu-Cortef; stabilnost med uporabo; študija prisilne razgradnje